2008
DOI: 10.1016/j.cej.2007.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of high-emissivity coatings in steam cracking furnaces using a non-grey gas radiation model

Abstract: The efficiency of the application of high-emissivity coatings on the furnace walls in steam cracking technology can only be evaluated on the basis of a description of radiative heat transfer distinguishing between the frequency bands. To this end, a non-grey gas radiation model based on the exponential wide band model (EWBM) has been developed and applied in the context of three-dimensional CFD simulations of an industrial naphtha cracking furnace with side-wall radiation burners. Applying a high-emissivity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…[9] and the formation of NO x emissions in steam crackers [10]. They also investigated the effect of high-emissivity coatings using a non-grey gas radiation model [11] and extended their model to a steam cracker convection section [12]. Guihua et al first reported a complete detailed coupled model of flow, combustion, radiative heat transfer and ethylene cracking reaction process which used a computational fluid dynamics (CFD) code [13].…”
Section: Introductionmentioning
confidence: 98%
“…[9] and the formation of NO x emissions in steam crackers [10]. They also investigated the effect of high-emissivity coatings using a non-grey gas radiation model [11] and extended their model to a steam cracker convection section [12]. Guihua et al first reported a complete detailed coupled model of flow, combustion, radiative heat transfer and ethylene cracking reaction process which used a computational fluid dynamics (CFD) code [13].…”
Section: Introductionmentioning
confidence: 98%
“…High infrared emissivity materials have widely been used in energy conservation equipment or thermal protective system [12][13][14]. In recent years, many attentions have been attracted to improve the infrared emissivity by changing the factors of component, crystalline size, heat treatment, doping [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, modeling of radiative heat transfer in the CFD solver necessitates an accurate and computationally efficient nongray radiative property estimation technique for all combustion environments. To achieve this objective, accuracy of different nongray WSGGM [10][11][12][13][14][15] and full-spectrum k-distribution method [16] was tested by comparing their predictions against those of gray WSGGM, all coupled with ANSYS FLUENT for different test cases. These studies imply that nongray gas radiative properties are necessary when modeling air-fuel, oxy-fuel, or oxy-enriched combustion.…”
Section: Introductionmentioning
confidence: 99%